Effects of Ge-132 and GeO2 on seed germination and seedling growth of Oenothera biennis L. under NaCl stress. Issue 1 (2nd January 2017) - Liu, Yan; Hou, Long-yu; Li, Qing-mei; Jiang, Ze-ping; Gao, Wei-dong; Zhu, Yan; Zhang, Hai-bo
ABSTRACT: To investigate the effects of β -carboxyethyl germanium sequioxide (Ge-132) and germanium dioxide (GeO2 ) on improving salt tolerance of evening primrose ( Oenothera biennis L.), seed germination, seedling growth, antioxidase and malondialdehyde (MDA) were observed under treatments of various concentrations (0, 5, 10, 20, 30 μM) of Ge in normal condition and in 50 mM NaCl solution. The results showed that both Ge-132 and GeO2 treatments significantly increased seed germination percentage and shoot length in dose-dependent concentrations but inhibited early root elongation growth. 5–30 μM Ge-132 and 10, 20 μM GeO2 treatments could significantly mitigate even eliminate harmful influence of salt, representing increased percentage of seed germination, root length, ratio between length of root and shoot, and decreased shoot length. These treatments also significantly decreased peroxidase (POD) and catalase (CAT) activities and MDA content. The mechanism is likely that Ge scavenges reactive oxygen species – especially hydrogen peroxide (H2 O2 ) – by its electron configuration 4S 2 4P 2 so as to reduce lipid peroxidation. This is the first report about the comparison of bioactivity effect of Ge-132 and GeO2 on seed germination and seedling growth under salt stress. We conclude that Ge-132 is better than GeO2 on promoting salt tolerance of seed and seedling.